Difficulties in Extracting Dentures Stuck in The Esophagus - Tamin, Susyana; Habib, Hasnan (Dentistry Faculty, 2024)
Foreign bodies in the esophagus are one of the common problems that ENT doctors often face. One of them is a foreign body with dentures in the esophagus. The diagnosis of a foreign body of dentures in the esophagus is established based on anamnesis, physical examination, radiological examination, and esophagoscopy. The act of esophagoscopy is performed as diagnostic and therapeutic. If not handled immediately and adequately, foreign bodies in the esophagus can cause complications such as esophageal perforation, blockage, and pressure of the foreign body into the airway and other complications. Patient readiness, availability of tools, and the presence of experienced experts are significant factors in overcoming this case. Prompt treatment using esophagoscopy is a safe and effective way to perform foreign body extraction in most cases. Thoracotomy to esophagectomy is performed in cases of foreign bodies in the esophagus that experience difficulties or failure in extracting by esophagoscopy. It was reported that two cases of foreign bodies with dentures in the esophagus were removed by thoracotomy accompanied by esophagectomy.